16.8k views
2 votes
Find the integral, using techniques from this or the previous chapter.
∫3x/√x-2 dx.

User Ludger
by
5.2k points

1 Answer

5 votes

Answer:


2(x-2)^{(3)/(2)}+12√(x-2)+C

Explanation:

Given:

The expression to integrate is given as:


\int (3x)/(√(x-2))\ dx

Now, in order to integrate it, we apply the method of substitution.

Let
x-2=t^2


x=t^2+2

Differentiating with respect to 't' on both sides, we get:


(dx)/(dt)=2t+0\\(dx)/(dt)=2t\\dx=2tdt

Replace
dx by
2tdt,
x-2\ by\ t^2 and
x by
t^2+2. This gives,


\int (3(t^2+2))/(√(t^2))\ 2tdt\\\\6\int ((t^2+2)t)/(t)\ dt\\\\6\int (t^2+2)\ dt\\\\6[(t^3)/(3)+2t]+C\\\\2t^3+12t+C

Replacing 't' by
√(x-2), we get:


=2(x-2)√(x-2)+12√(x-2)+C


2(x-2)^{(3)/(2)}+12√(x-2)+C

Therefore, the integral is:


\int (3x)/(√(x-2))\ dx=2(x-2)^{(3)/(2)}+12√(x-2)+C

Where 'C' is the constant of integration.

User Steven Johnston
by
5.0k points